A review of the massive Chilean palm Jubaea chilensis - Eduardo Guzmán; José Antonio Alcalde; Samuel Contreras; M. Paulina Fernández (Caldasia)
Diverse information about the Chilean palm Jubaea chilensis, an endemic species to the Chilean Mediterranean ecosystem, has been generated along the two last centuries. The objective of this review is to bring together in a single document all the information to date on this species. Diverse sources of information were considered, from where the information gathered was systematized and analyzed to be presented in five broad themes. J. chilensis belongs to the Arecaceae family, and can reach 33 m height and two m in diameter, making it one of the most massive palms. Is the southernmost palm in the Americas, and because of its massiveness, it can resist prolonged periods of drought and low temperatures. Therefore, the species is used ornamentally in many countries. Its original population has decreased dramatically in recent centuries due to land use conversion and harvesting. Although it is now a protected species, the Chilean palm is classified as having vulnerable preservation status. Its principal threats, as indiscriminate fruit harvesting and the decreased of vegetal cover, have led to the aging of the palm population without proper regeneration. More research at the species level is highly recommended. Three broad thematic areas should be the focus for deepening the knowledge about the species: biology, specifically in terms of ecophysiology and reproduction; determine its environmental requirements; and, resulting from the application of the knowledge of the first two themes, the reconstruction of its natural populations.